Type of Referral, Dialysis Start and Choice of Renal Replacement Therapy Modality in an International Integrated Care Setting. - Belén Marrón; Janusz Ostrowski; Marietta Török; Delia Timofte; Attila Orosz; Andrzej Kosicki; Alicja Całka; Daniela Moro; Dezider Kosa; Jenö Redl; Abdul Rashid Qureshi; Jose Carolino Divino-Filho; et al. (PLoS ONE, 2016)
INTRODUCTION:Integrated Care Settings (ICS) provide a holistic approach to the transition from chronic kidney disease into renal replacement therapy (RRT), offering at least both types of dialysis. OBJECTIVES:To analyze which factors determine type of referral, modality provision and dialysis start on final RRT in ICS clinics. METHODS:Retrospective analysis of 626 patients starting dialysis in 25 ICS clinics in Poland, Hungary and Romania during 2012. Scheduled initiation of dialysis with a permanent access was considered as planned RRT start. RESULTS:Modality information (80% of patients) and renal education (87%) were more frequent (p<0.001) in Planned (P) than in Non-Planned (NP) start. Median time from information to dialysis start was 2 months. 89% of patients started on hemodialysis, 49% were referred late to ICS (<3 months from referral to RRT) and 58% were NP start. Late referral, non-vascular renal etiology, worse clinical status, shorter time from information to RRT and less peritoneal dialysis (PD) were associated with NP start (p<0.05). In multivariate logistic regression analysis, P start (p≤0.05) was associated with early referral, eGFR >8.2 ml/min, >2 months between information and RRT initiation and with vascular etiology after adjustment for age and gender. "Optimal care," defined as ICS follow-up >12 months plus modality information and P start, occurred in 23%. CONCLUSIONS:Despite the high rate of late referrals, information and education were widely provided. However, NP start was high and related to late referral and may explain the low frequency of PD.